Biomechanical Evaluation and the Assisted 3D Printed Model in the Patient-Specific Preoperative Planning for Thoracic Spinal Tuberculosis: A Finite Element Analysis - Bingjin Wang; Wencan Ke; Wenbin Hua; Xianlin Zeng; Cao Yang (Frontiers in Bioengineering and Biotechnology, 2020)
Posterior fixation is superior to anterior fixation in the correction of kyphosis and maintenance of spinal stability for the treatment of thoracic spinal tuberculosis. However, the process of selecting the appropriate spinal fixation method remains controversial, and preoperative biomechanical evaluation has not yet been investigated. In this study, we aimed to analyze the application of the assisted finite element analysis (FEA) and the three-dimensional (3D) printed model for the patient-specific preoperative planning of thoracic spinal tuberculosis. An adult patient with thoracic spinal tuberculosis was included. A finite element model of the T7−T11 thoracic spine segments was reconstructed to analyze the biomechanical effect of four different operative constructs. The von Mises stress values of the implants in the vertical axial load and flexion and extension conditions under a 400-N vertical axial pre-load and a 10-N⋅m moment were calculated and compared. A 3D printed model was used to describe and elucidate the patient’s condition and simulate the optimal surgical design. According to the biomechanical evaluation, the patient-specific preoperative surgical design was prepared for implementation. The anterior column, which was reconstructed with titanium alloy mesh and a bone graft with posterior fixation using seven pedicle screws (M+P) and performed at the T7–T11 level, decreased the von Mises stress placed on the right rod, T7 pedicle screw, and T11 pedicle. Moreover, the M+P evaded the left T9 screw without load bearing. The 3D printed model and preoperative surgical simulation enhanced the understanding of the patient’s condition and facilitated patient-specific preoperative planning. Good clinical results, including no complication of implants, negligible loss of the Cobb angle, and good bone fusion, were achieved using the M+P surgical design. In conclusion, M+P was recommended as the optimal method for preoperative planning since it enabled the preservation of the normal vertebra and prevented unnecessary internal fixation. Our study indicated that FEA and the assisted 3D printed model are tools that could be extremely useful and effective in the patient-specific preoperative planning for thoracic spinal tuberculosis, which can facilitate preoperative surgical simulation and biomechanical evaluation, as well as improve the understanding of the patient’s condition.